The Old Testament between diachrony and synchrony : two reasons for favouring the former - Lombaard, Christo (Journal for semitics, 2006)
Arguments in narrative and structuralist readings as an alternative to the historical-critical readings of the Old Testament are prove to be incorrect. C Lombaard offer 2 reasons - one methodological and one theological as to why the historical-critical approaches remain preferable. 1. A-The prefered